Bamboo cellulose nanocrystals inserted in the composition of cementitious mortars - Hashimoto, Beatriz Fabrega (2022)
This research deals with obtaining nanocrystals of cellulose from eucalyptus, which aims to insert and increase the strength of mortar, using nanotechnology for its improvement as an alternative way to reinforce the composition of the material. The methodology used to obtain this is a chemical treatment that must be carried out in two stages. The first is an alkaline treatment using sodium hydroxide (NaOH) and the second part, which is where the result is obtained, is acid hydrolysis using sulfuric acid (H2SO4). Briefly, cellulose, a polymer that is very abundant on the earth, when chemically treated becomes a material that can satisfactorily improve the strength of mortar or any other cementitious material. Its use in the future as a form of improvement, will become of paramount importance in civil construction, because it helps in the improvement of one of the most used materials in the industry in order to think about sustainability.